Mobile-web based electronic health records system for ICU patient management in heart hospital - Sarwar, Hasan; Rahman, Mizanur; Hasan, Mohammad Nurul Akhtar (Institute of Electrical and Electronics Engineers Inc., 2023)
Heart disease is a major public health issue that requires timely and accurate diagnosis, treatment, and follow-up of patients. However, many healthcare providers and patients face challenges in accessing and updating health information, especially in resource-limited settings. This paper presents the design, development, and evaluation of a novel Mobile-Web-based electronic health records system (MWEHRS) that leverages the advantages of both mobile and web technologies to provide a user-friendly, secure, and scalable system for patient management in heart diseases. Through this research a real system has been implemented in National Heart Foundation Hospital, Bangladesh. MWEHRS allows healthcare providers and patients to access and update health information using any device with an internet connection, such as smartphones, tablets, or computers. The developed system also integrates various features and functionalities to support the diagnosis, treatment, and follow-up of heart disease patients. The system provides automation to calculate some parameters and thus relieves the attending nurses from doing so. The developed system enables doctors to watch patient status in real time and take decisions with ease both during and after the course of therapy.